Pelatihan Keterampilan di Bidang Pekerjaan Kayu sebagai Upaya Peningkatan Pemberdayaan SDM di Desa Kucur Kabupaten Malang - Yuaniar, Maria Carolina ; Pangastuti Ardiani, Dyah Ayu ; Nofrin, Muhammad Fadil ; Zuhdi, Mochammad Komaruddin ; Ihza Mahendra, Yusril Dwi; Wasito, Hadi (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
The village of Kucur is located in Dau district of Malang Regency, located on the edge of the forest making this village has the most wood industry no 2 in Malang district. Education of Kucur villagers on average only up to junior high school graduates and about 47.8% are elementary school graduates (BPS Kabupaten malang, 2017), low education plus the condition of areas that do not have tourist attractions so the people's sphere tends to factory workers and builders building (Laksono, 2014). Whereas with the natural potential that people should utilize optimally, plus the community has the basic skills in the field of wood, hence can be utilized by honing the skills of the community in the field of wood by held Skills Training Program in Wood Industry at Karang Taruna Klaseman Village Kucur. The training phases that will be held in this program are design training, woodworking technique training and marketing technique training. From the questionnaire data on the pre test, the result of the lack of public knowledge about the training stage will be given so that more people who do not know about the stages of furniture business and the interest of the program is very high and post test result is the community understanding about the multifunctional wood working technique, product design and marketing technique is high enough that this makes the program successful and 100% of the results of this program successfully invites the community to continue business in the field of wood industry.